Small Structures Bring Big Things: Performance Control of Hollow Multishelled Structures. Issue 1 (19th October 2020) - Wang, Li; Wan, Jiawei; Wang, Jiangyan; Wang, Dan
Abstract : Hollow multishelled structures (HoMSs) have gained numerous achievements in broad scientific research fields. In the past decade, the rapid developments of synthetic methods and advanced characterization technologies have enriched HoMS family with abundant chemical compositions and geometric structures. In addition, the control in phase structure and surface structure of HoMSs have also been reported in recent years. With great efforts devoted to controlling the compositional and structural characteristics, such as shell composition, shell number, shell thickness, and intershell space, HoMSs have displayed their intrinsic temporal–spatial nature and proven to be fruitful in optimizing mass transport, storage, and release. This review first summarizes the compositional and structural control of HoMSs in three levels, that is, building subunits, assembled functional shells, and HoMSs. Subsequentially, the essential influence of composition and structure on mass transport, storage, and release is deeply discussed by highlighting the application of HoMSs in energy storage, catalysis, electromagnetic wave absorption, and drug delivery. Finally, the challenges and opportunities in the future development of HoMSs are forecasted. Abstract : Hollow multishelled structures (HoMSs) have gained numerous achievements in broad applications. The composition and structure control in the subunits, shells and HoMSs as well as performance control of HoMSs are summarized in this review, which demonstrates the essential effect of compositions and structures on performance properties of HoMSs and helps to guide HoMSs design targeted to specific application requirements.